Q. 64.5( 11 Votes )

If cosec θ – sin

Answer :

Formula: - (i) a3 + b3 = (a + b)3 – 3 a b (a + b)


(ii) Sin2θ + Cos2θ = 1


Given : -


Cosecθ - sinθ = l


Secθ – Cosθ = m


We have to prove that : l2 m2 (l2 + m2 + 3) = 1


Cosecθ – sinθ = l



And secθ – Cosθ = m




putting (a)and(b)




Multiplying with



= (cos2θ)3 + ( sin2θ)3 + 3sin2θCos2θ




l2 m2 (l2 + m2 + 3) = 1


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses